2022
DOI: 10.1101/2022.03.07.483298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic Profiling of Hypoplastic Lungs Suggests an Underlying Inflammatory Response in the Pathogenesis of Abnormal Lung Development in Congenital Diaphragmatic Hernia

Abstract: The pathogenesis of lung hypoplasia in congenital diaphragmatic hernia (CDH), a common birth defect, is poorly understood. The diaphragmatic defect can be repaired surgically, but the abnormal lung development contributes to a high mortality in these patients. To better understand the underlying pathobiology, we used the nitrofen rat model of CDH and characterized the proteome of hypoplastic CDH lungs at the alveolar stage (E21). Amongst the 218 significantly altered proteins between CDH and control lungs were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moreover, using the nitrofen model, some studies have reported that rat fetuses with CDH had lung inflammatory changes such as high levels of monocyte chemoattractant protein-1 (Mcp1; also known as chemokine C-C motif ligand 2, Ccl2) and Tnfα (65)(66)(67). A recent study employing unbiased proteomics on the lungs of rat fetuses with CDH showed elevated levels of inflammatory mediators such as STAT3 compared to non-CDH controls (68). Our snRNA-seq experiments showed that all four major lung cell types in CDH fetuses had upregulation of several inflammatory mediators, including Tnfα, Stat3, and chemokines Ccl3/4 and Cxcl1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using the nitrofen model, some studies have reported that rat fetuses with CDH had lung inflammatory changes such as high levels of monocyte chemoattractant protein-1 (Mcp1; also known as chemokine C-C motif ligand 2, Ccl2) and Tnfα (65)(66)(67). A recent study employing unbiased proteomics on the lungs of rat fetuses with CDH showed elevated levels of inflammatory mediators such as STAT3 compared to non-CDH controls (68). Our snRNA-seq experiments showed that all four major lung cell types in CDH fetuses had upregulation of several inflammatory mediators, including Tnfα, Stat3, and chemokines Ccl3/4 and Cxcl1.…”
Section: Discussionmentioning
confidence: 99%
“…The FETO procedure is proven to be of considerable survival benefit to the most severely affected patients; however, there is the need to identify predictive functional biomarkers, as survival remains poor. Notably, around 60% of severe patients do not survive to discharge from hospital 66 .…”
Section: Discussionmentioning
confidence: 99%
“…34 Moreover, there is increasing evidence that fetuses with CDH have an inflammatory profile that one could speculate to be the result of a viral infection. 35,36 A study on maternal and cord blood samples from fetuses with CDH and unaffected controls showed that CDH neonates have an upregulation of inflammatory mediators. 35 A more recent study analyzing the proteomic profile of tracheal aspirates obtained at the time of fetal endoscopic tracheal occlusion showed that CDH survivors had a worse inflammatory profile compared with nonsurvivors (►Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…35 A more recent study analyzing the proteomic profile of tracheal aspirates obtained at the time of fetal endoscopic tracheal occlusion showed that CDH survivors had a worse inflammatory profile compared with nonsurvivors (►Table 2). 36 The variations in seasonality in other congenital anomalies reported in the literature have been attributed to other environmental factors beyond viruses. Boyd et al reported that hypoplastic left heart syndrome and coarctation of the aorta have seasonal variations in incidence which could be ascribed to ultraviolet light exposure, variations in nutrition, and in the use of agricultural chemicals.…”
Section: Discussionmentioning
confidence: 99%